273 Molecular Characteristics of Methicillin Resistant Staphylococcus Aureus Isolated from Chinese Children. (October 2012) - Shen, X; Liu, Y
Abstract : Objective: The present study aim to investigate the molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA) isolates from Chinese children in seven city. Method: A total of 134 MRSA isolats were collected from eight hospitals. Multilocus sequence (MLST), staphylococcal chromosomal cassette mec (SCCmec) and spa typing were analyzed. The Panton-Valentine leukocidin (pvl) gene was also detected. Result: Overall, 16 sequence types (STs) were obtained, and CC59 (51.7%) was found to be the most prevalent, which including ST59 and ST338, followed by ST239 (16.4%). SCCmec type II, III, IV and V were identified in this study. SCCmec type IV was the most predominant type at 50.0%, followed by SCCmec type V at 23.9% and III at 23.9%. SCCmec subtypes IVa, IVc, and IVg were found among the SCCmec type IV strains, IVa was the main subtype at 77.6%. Twenty-six spa types were also identified, the predominant type was t437 (47.8%). The prevalence of pvl genes and the SCCmec type of the strain were relevant, the pvl gene positive rate was higher in SCCmecIV and V-type strains than in SCCmecII and III-type strains (58.6% vs. 14.3%, P<0.05); there was a significant difference between them. In the strains isolates from pneumonia and SSTIs, ST59-MRSA-Iva (t437) was the predominnant clone. Conclusion: The result indicates that MRSA isolates in Chinese children are largely associated with the ST59-MRSA-IV (t437) and ST239-MRSA-III (t037) clone.